PENERAPAN HABITUS PADA POTENSI DAN MODEL PENGEMBANGAN WISATA SPIRITUAL ALAS METAPA DESA PENINJOAN, KECAMATAN TEMBUKU, KABUPATEN BANGLI - Ketut Muliadiasa, I; Putu Isha Aprinica, Ni (SIWAYANG Journal: Publikasi Ilmiah Bidang Pariwisata, Kebudayaan, dan Antropologi, 2022)
The selection of alternative tourism development is one form that can be done in realizing tourism development by exploring the natural potential of the countryside into a tourist village. The quality of life of the community can be seen from the lifestyle which is the main ingredient. Building a tourist village which must be able to explore the unique potential of the village so that it has a characteristic that can motivate tourists in the future. The involvement of local communities in the development of tourist villages is a very appropriate form of formulation for the sustainability of the development of the tourist village. The spiritual tourism village of Alas Metapa Paninjoan has a lot of potential that can be developed but has not been explored optimally. The natural potential of natural and spiritual tourism objects. The crafts of the people of Paninjoan Tourism Village are in the form of farming and gardening in addition to traders who produce very adequate oyster mushrooms. The attractions that become the attraction of the Paninjoan tourist village are visiting people's homes to see firsthand the making of oyster mushrooms and the packaging process in addition to visiting Pancoran 11 with soft holy water and the Alas Metapa Temple, Bukit Hill and Pondok Mahapraja.